AKUNTABILITAS GURU - Simanungkalit, Misran (IAIN PADANGSIDIMPUAN, 2013)
The accountability of teacher is urge competition for each teacher in education and teacher presses. The Competency of education, ethic readiness, knowledge, and professional of teach group is cualification of teacher.